A highly spatially resolved GIS-based model to assess the isoprenoid emissions from key Italian ecosystems - Pacheco, Claudia Kemper; Fares, Silvano; Ciccioli, Paolo (Atmospheric Environment, 2014)
The amount of Biogenic Volatile Organic Compounds (BVOC) emitted from terrestrial vegetation is of great importance in atmospheric reactivity, particularly for ozone-forming reactions and as condensation nuclei in aerosol formation and growth. This work presents a detailed inventory of isoprenoid emissions from vegetation in Italy using an original approach which combines state of the art models to estimate the species-specific isoprenoid emissions and a Geographic Information System (GIS) where emissions are spatially represented. Isoprenoid species and basal emission factors were obtained by combining results from laboratory experiments with those published in literature. For the first time, our investigation was not only restricted to isoprene and total monoterpenes, but our goal was to provide maps of isoprene and individual monoterpenes at a high-spatial (∼1 km2) and temporal resolution (daily runs, monthly trends in emissions are discussed in the text). Another novelty in our research was the inclusion of the effects of phenology on plant emissions. Our results show that: a) isoprene, a-pinene, sabinene and b-pinene are the most important compounds emitted from vegetation in Italy; b) annual biogenic isoprene and monoterpene fluxes for the year 2006 were ∼31.30 Gg and ∼37.70 Gg, respectively; and c) Q. pubescens+Q. petrea+Q. robur, Q. ilex, Q. suber and Fagus sylvatica are the principal isoprenoid emitting species in the country. The high spatial and temporal resolution, combined with the species-specific emission output, makes the model particularly suitable for assessing local budgets, and for modelling photochemical pollution in Italy.
Keywords: BVOC inventory; isoprene; Isoprenoids; Italian forests; Monoterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Volatile organic compound emissions in relation to plant carbon fixation and the terrestrial carbon budget - Kesselmeier, Jürgen; Ciccioli, Paolo; Kuhn, Uwe; Stefani, Paolo; Biesenthal, Thomas; Rottenberger, Stefanie; Wolf, Annette; Vitullo, Marina; Valentini, Ricardo; Nobre, Antonio; Kabat, Pavel; Andreae, Meinrat O. (Global Biogeochemical Cycles, 2002)
A substantial amount of carbon is emitted by terrestrial vegetation as biogenic volatile organic compounds (VOC), which contributes to the oxidative capacity of the atmosphere, to particle production and to the carbon cycle. With regard to the carbon budget of the terrestrial biosphere, a release of these carbon compounds is regarded as a loss of photosynthetically fixed carbon. The significance of this loss for the regional and global carbon cycles is controversial. We estimate the amount of VOC carbon emitted in relation to the CO2 taken up, based on our own enclosure and micrometeorological flux measurements of VOC emissions and CO2 exchange within the Mediterranean area and the tropical rainforest in Amazonia and on literature data. While VOC flux estimates are small in relation to net primary productivity and gross primary productivity, the amount of carbon lost as VOC emissions can be highly significant relative to net ecosystem productivity. In fact, VOC losses are of the same order of magnitude as net biome productivity. Although we must assume that large amounts of these reemissions are recycled within the biosphere, a substantial part can be assumed to be lost into longer-lived oxidation products that are lost from the terrestrial biosphere by transport. However, our current knowledge does not allow a reliable estimation of this carbon loss.
Keywords: carbon cycle; volatile organic compounds (VOC)

A hypothesis on the evolution of isoprenoid emission by oaks based on the correlation between emission type and Quercus taxonomy - Loreto, Francesco; Ciccioli, Paolo; Brancaleoni, Enzo; Valentini, Riccardo; De Lillis, Manuela; Csiky, Olav; Seufert, Guenther (Oecologia, 1998)
We show that Mediterranean oaks that emit isoprene, monoterpenes or no isoprenoids belong to dierent subgenera as indicated by morpho-taxonomy and molecular genetics. On the other hand, oaks from North America and Asia that are taxonomically similar to the Mediterranean monoterpene emitter Q. ilex emit isoprene only. We surmise that isoprene emission is a genetic character which evolved ancestrally in the oak genus since this is the prevalent emission type in oaks widespread around the world and adapted to dierent environments. This ancestral character may have been either lost or modi®ed in more recent clades such as those originating the Mediterranean oaks. If our hy- pothesis is correct then the taxonomy of European oaks is validated by this independent trait. Isoprenoid emis- sion could serve as a chemo-taxonomical marker and could be used to reconstruct the phylogeny of oaks in association with molecular markers.
Keywords: chemo-taxonomy; Evolution; isoprenoid emission; Quercus

Measurement of isoprenoid content in leaves of Mediterranean Quercus spp. by a novel and sensitive method and estimation of the isoprenoid partition between liquid and gas phase inside the leaves - Loreto, Francesco; Ciccioli, Paolo; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano (Plant Science, 1998)
We used a novel. simple and sensitive method to extract isoprenoids contained in the leaves and compared emission and content of isoprenoids in the leaves of three Mediterranean oak species emitting isoprene (Quercus puhcsccws), monoterpenes (Querc~s ilrs) or non-emitting isoprenoids (Quercus cerris). The content is qualitatively consistent with the emission of isoprenoids by Qucrczls spp. However. the fraction of isoprenoids in the gas phase was estimated to be r 0.02 and 5% of the total content for monoterpenes and isoprene, respectively. On the other hand, the content of monoterpenes in the leaf was much higher than that of isoprene and particularly rich of compounds which can hardly be detected in an emission such as linalool. It is concluded that isoprenoids are contained in temporary pools and that the different partition between gas and liquid phases plays an important role in determining the pool size in isoprene and monoterpene-emitting oaks. The pools of isoprenoid-emitting oaks sustain the emission for few minutes when isoprenoid formation is prevented. which rules out the presence of specialized organs for isoprenoid storage and are absent altogether in non-emitting species.
Keywords: Isoprene emission (content); Monoterpene emission (content): Quercus spp.

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature